Evaluation of diagnosis and treatment practices of Brazilian neurologists among patients with multiple sclerosis - Cássia Elisa Marin; Dagoberto Callegaro; Marco Aurélio Lana-Peixoto; Oscar Fernández; Antonio Pereira Gomes Neto; Claudia Cristina Ferreira Vasconcelos; José Artur Costa d’Almeida; Marcus Vinícius Magno Gonçalves; Maria Fernanda Mendes; Mônica Koncke Fiuza Parolin; Osvaldo Nascimento; Paulo Diniz da Gama; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Recent changes to the diagnostic criteria for multiple sclerosis (MS) and new medications have had a major impact on the way in which specialists manage the disease. Objective: To investigate factors considered by Brazilian neurologists in managing MS, and to identify how these contribute to diagnosis and treatment. Methods: Potential participants were selected by a steering committee (MS experts who developed this survey). Only MS specialists were included in the study (neurologists who had completed a neuroimmunology fellowship or who were treating more than 30 MS patients). Links to the online questionnaire were distributed between March 2019 and January 2020. This questionnaire was composed of sections with hypothetical MS scenarios. Results: Neurologists from 13 Brazilian states responded to the survey (n = 94). In the clinically isolated syndrome (CIS) scenario, the respondents agreed to treat patients with a high risk of MS diagnosis, whereas in the radiologically isolated syndrome (RIS) half of the respondents opted not to treat, even among high-risk patients. In cases of low-activity relapsing-remitting MS (RRMS), the choice of treatment was distributed among interferon beta, glatiramer acetate and teriflunomide, which were changed to fingolimod and natalizumab, as RRMS severity increased. The topics in which disagreement was found included practices regarding use of disease-modifying therapy (DMT) for pregnant patients and the washout period required for some DMTs. Conclusions: This study enabled identification of areas of agreement and disagreement about MS treatment among Brazilian neurologists, which can be used to update future protocols and improve patient management.